Media Freedom and Pluralism - Beata Klimkiewicz (Central European University Press, 2010)
Media policy in Europe faces a twofold challenge. On the one hand, new technologies and media services such as digital television, satellite radio, mobile content applications, video on demand, and new Internet services are fundamentally transforming media environments and media use. On the other hand, the historical enlargement integrating the countries of Eastern and Central Europe within the EU’s political, economic, and legal structures implies fundamental geopolitical and cultural change, both at the European level and in the region. These new conditions in the making can be approached in one of three ways: either through a chronological description of different consecutive stages (a historical approach); through a case-by-case description of different national or country experiences (a geographical approach), or through an analytical approach aiming at conceptualizing main problem areas and open questions in European media policy today. As can be surmised from the table of contents, the authors of this volume followed the third route. This choice, however, does not eliminate time and space considerations at the expense of a problem-oriented focus. Differentiation and delineation of problem areas is deeply rooted in an emerging logic of media policy, which requires a new type of complexity. In other words, national borders still matter, but so do sub-national (regional), supranational and global constellations. A new complexity thus depends on switching between different spatial, cultural, and political levels and constant redefinition of their institutional settings and fields of competencies. The dynamics of globalization